Capabilities and the Definition of Health Comments on Venkatapuram - Richardson, Henry S.; Venkatapuram, Sridhar (2016)
Sridhar Venkatapuram's Health Justice argues that health is a ‘metacapability’ - specifically, as the metacapability of having the ten ‘central human capabilities’ described by Martha Nussbaum. This cannot be right, as it provides no basis for distinguishing health from education, riches, or love. An amendment correcting this problem is suggested, namely that health is the involuntary, bodily aspect of the metacapability for the central capabilities. This amendment is defended against the objection that it fails to capture some important aspects of mental health.
Keywords: Amartya Sen; Christopher Boorse; Lennart Nordenfelt; Martha Nussbaum; Capabilities; Health; Rezension